PENGARUH BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN, JASA BISNIS, TRANSPORTASI (KASUS PO.MEDAN JAYA PERWAKILAN PEKANBARU) - Sanjaya "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research to knowing the effect of Brand Image and service quality for the loyalty of costumer, business service, transportation in the case of PO. Medan Jaya Brand Image Branch Pekanbaru. Brand Image as a Variable (X1) and service quality as (X2) and then can formulate at the step of implementation of the activity,equiment that used, standard or parameter that has appointed, The test and inspection. And then the loyalty of costumer as a the dependent variable (Y). This research is doing for every passengers or everyone who know the Bus PO. Medan Jaya as many as 99 persons. The Data obtained from questionnaire and the next to be treated for being tested use statistic analysis such assimple linear regression analysis, t test, and correlation analysis and determination with use the help of SPSS 17.The result of research show that the result of hypotesis test t thitung 4,652>ttabel 1,985. This case show thatBrand Image give the effect on Loyalty of costumers, and the test result thitung 7,259>ttabel 1,985. This case show that the service quality give the effect onloyalty of bus costumers PO. Medan Jaya is equal to 68,1%Keywords: Brand Image ,Service Quality, Loyalty of costumer